MANAJEMEN SATUAN PENDIDIKAN BERBASIS OUTCOME-BASED EDUCATION DALAM MENGHASILKAN LULUSAN BERKUALITAS - Feisal Leonard Ridwanullah; Gerry Pratama; Muhammad Zulfikar (STKIP Subang, 2026)
This research examines the implementation of Outcome-Based Education (OBE) management in educational institutions to produce quality graduates. Using a qualitative descriptive case study approach at SDI Hasyim Asy'ari Cisarua Bogor, this study explores how OBE-based educational management is planned, implemented, and evaluated. Data were collected through in-depth interviews, participatory observation, and documentation analysis. The findings indicate that OBE-based educational management requires clear outcome identification, backward curriculum design, student-centered learning strategies, and authentic assessment systems. The implementation involves transformation from teacher-centered to student-centered approaches, development of professional teacher competencies, and creation of a conducive learning environment. The evaluation system focuses on measuring learning achievement comprehensively through criterion-referenced assessment and continuous quality improvement. This research contributes to understanding how OBE principles can be contextualized in Islamic primary education settings and provides practical implications for improving educational quality through outcome-oriented management approaches.